W transport and accumulation control in the termination phase of JET H-mode discharges and implications for ITER. (5th June 2018) - Köchl, F; Loarte, A; de la Luna, E; Parail, V; Corrigan, G; Harting, D; Nunes, I; Reux, C; Rimini, F G; Polevoi, A; Romanelli, M
Abstract: Tokamak operation with W PFCs is associated with specific challenges for impurity control, which may be particularly demanding in the transition from stationary H-mode to L-mode. To address W control issues in this phase, dedicated experiments have been performed at JET including the variation of the decrease of the power and current, gas fuelling and central ion cyclotron heating (ICRH), and applying active ELM control by vertical kicks. The experimental results obtained demonstrate the key role of maintaining ELM control to control the W concentration in the exit phase of H-modes with slow (ITER-like) ramp-down of the neutral beam injection power in JET. For these experiments, integrated fully predictive core+edge+SOL transport modelling studies applying discrete models for the description of transients such as sawteeth and ELMs have been performed for the first time with the JINTRAC suite of codes for the entire transition from stationary H-mode until the time when the plasma would return to L-mode focusing on the W transport behaviour. Simulations have shown that the existing models can appropriately reproduce the plasma profile evolution in the core, edge and SOL as well as W accumulation trends in the termination phase of JET H-mode discharges as function of the applied ICRH and ELM control schemes, substantiating the ambivalent effect of ELMs on W sputtering on one side and on edge transport affecting core W accumulation on the other side. The sensitivity with respect to NB particle and momentum sources has also been analysed and their impact on neoclassical W transport has been found to be crucial to reproduce the observed W accumulation characteristics in JET discharges. In this paper the results of the JET experiments, the comparison with JINTRAC modelling and the adequacy of the models to reproduce the experimental results are described and conclusions are drawn regarding the applicability of these models for the extrapolation of the applied W accumulation control techniques to ITER.